2014
DOI: 10.1292/jvms.13-0398
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Effects of Atipamezole, Yohimbine and Prazosin on Medetomidine-Induced Diuresis in Healthy Cats

Abstract: This study aimed to investigate and compare the antagonistic effects of atipamezole, yohimbine and prazosin on medetomidine-induced diuresis in healthy cats. Five cats were repeatedly used in each of the 9 groups. One group was not medicated. Cats in the other groups received 40 µg/kg medetomidine intramuscularly and saline (as the control), 160 µg/kg prazosin, or 40, 160 or 480 µg/kg atipamezole or yohimbine intravenously 0.5 hr later. Volume, pH and specific gravity of urine; plasma arginine vasopressin (AVP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…When it comes to managing Xylazine-induced hypotension and diuresis, many patients respond well to intravenous (IV) fluids alone, without the need for additional interventions [ 19 , 20 ]. Animal studies have demonstrated that Xylazine can cause diuresis, which can be reversed by Atipamezole and yohimbine [ 59 ].…”
Section: Reviewmentioning
confidence: 99%
“…When it comes to managing Xylazine-induced hypotension and diuresis, many patients respond well to intravenous (IV) fluids alone, without the need for additional interventions [ 19 , 20 ]. Animal studies have demonstrated that Xylazine can cause diuresis, which can be reversed by Atipamezole and yohimbine [ 59 ].…”
Section: Reviewmentioning
confidence: 99%
“…A dose ratio of 1:1 was used experimentally in healthy cats to assess the effects of different atipamezole doses on medetomidineinduced diuresis, but the authors do not comment on the sedative effects or antagonism thereof for this dose. 15 A recent paper assessed the haemodynamic effects of 'lowdose' intravenous atipamezole following dexmedetomidine infusion in anaesthetised cats, but the effects of 'low-dose' atipamezole on sedation reversal and recovery time were not assessed. 16 Concerns regarding the adverse effects of ketamine on recovery quality owing to its ability to induce dysphoria, excitation, ataxia and muscle hypertonus have previously been raised.…”
Section: Effects Of Atipamezole Dosage and Timing Of Administration Omentioning
confidence: 99%
“…202 Prolonged confinement without opportunities for urination and defecation away from the enclosure can increase patient stress and discomfort. This problem may be exacerbated by perioperative administration of fluids and certain anesthetic agents such as α 2 -adrenoceptor agonists, 256,257 which can increase urine output. In addition, confinement inhibits elimination behavior in some patients.…”
Section: Return To Patient Housingmentioning
confidence: 99%